Programmed cell death 1 inhibitor plus chemotherapy vs. chemotherapy in advanced drive-gene-negative non-small-cell lung cancer patients: A real-world study - Li, Ying; Yang, Peng; Zhou, Xiao; Yang, Xuefeng; Wu, Shijie (Frontiers in Surgery, 2022)
Objective Programmed cell death 1 (PD-1) inhibitor has been in the market in China for several years, which lacks sufficient domestic evidence regarding its application in lung cancer. Thus, this study intended to assess the treatment outcome and tolerance of PD-1 inhibitor plus chemotherapy in advanced, driver-gene-negative, nonsquamous, non-small-cell lung cancer (NSCLC) patients in a real clinical setting. Methods This retrospective cohort study analyzed 68 advanced driver-gene-negative nonsquamous NSCLC patients, among which 38 cases received PD-1 inhibitor plus chemotherapy and 30 cases adopted chemotherapy alone. Disease control rate (DCR), objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and adverse events were reviewed. Results Generally, PD-1 inhibitor plus chemotherapy achieved a more satisfying ORR compared with chemotherapy alone (52.6% vs. 30.0%, P = 0.061), while the DCR did not vary between PD-1 inhibitor plus chemotherapy and chemotherapy (84.2% vs. 73.3%, P = 0.271). Patients receiving PD-1 inhibitor plus chemotherapy exhibited favorable PFS (median: 10.1 vs. 7.1 months, P = 0.040) and OS (median: 17.4 vs. 13.9 months, P = 0.049) than patients adopting chemotherapy alone. Additionally, after adjustment using multivariable Cox's analyses, PD-1 inhibitor plus chemotherapy (vs. chemotherapy) could independently realize prolonged PFS (P = 0.020) and OS (P = 0.029). Moreover, the majority of adverse events were manageable; meanwhile, grade 3–4 adverse events included leukopenia (13.2%), neutropenia (13.2%), nausea and vomiting (7.9%), anemia (5.3%), elevated transaminase (5.3%), thrombopenia (2.6%), anorexia (2.6%), peripheral neuropathy (2.6%), and rash (2.6%). Conclusion PD-1 inhibitor plus chemotherapy exhibits a better efficacy and equal tolerance compared with chemotherapy alone in advanced driver-gene-negative nonsquamous NSCLC patients.